Preparation method of anisotropic permanent magnetic ferrite magnet and permanent magnetic ferrite

By using solid lubricant and controlling moisture content during magnet preparation, the problems brought about by organic binders in magnet preparation are solved, and the preparation of high-performance dry-pressure opposite-sex magnets is realized, which improves the performance and environmental protection of magnets.

CN119874347APending Publication Date: 2025-04-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311373281.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, organic matter is used as binders, which has residuals, holes and environmental protection risks during magnet preparation, affecting the performance and safety of magnets.

Method used

By adding an appropriate amount of solid lubricant to the pre-magnetized magnetic powder and controlling the moisture content of the magnetic powder, using dry-pressure magnetic field molding and heat treatment processes, high-performance dry-pressure anisotropic sintered magnets are prepared, avoiding the use of organic binders.

Benefits of technology

The preparation of high-performance dry-pressure opposite-sex magnets is realized, which improves the magnetic performance and density of magnets, reduces the occurrence of dark cracks and holes, and eliminates the need for harmful organic binders, which improves the environmental protection and safety of production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004507064160000161
    Figure BDA0004507064160000161
  • Figure BDA0004507064160000171
    Figure BDA0004507064160000171
Patent Text Reader

Abstract

The invention provides a preparation method of an anisotropic permanent magnetic ferrite magnet and permanent magnetic ferrite.The preparation method comprises the steps that firstly, magnetic powder raw materials are subjected to pre-magnetization treatment, and pre-magnetized magnetic powder is obtained; (2) adding a lubricant into the pre-magnetized magnetic powder for primary mixing, and then adding a dispersion medium for secondary mixing to obtain anisotropic magnetic powder; and (3) carrying out dry-pressing magnetic field forming on the anisotropic magnetic powder to form an anisotropic magnet blank, and carrying out heat treatment to obtain the permanent magnetic ferrite. By adding a proper amount of the solid lubricant into the pre-magnetized magnetic powder and controlling the water content of the magnetic powder, the high-performance dry-pressing anisotropic sintered magnet can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic materials and relates to a preparation method of an anisotropic permanent ferrite magnet and the permanent ferrite. Background Art

[0002] Permanent magnetic materials refer to materials that can maintain constant magnetism once magnetized, also known as hard magnetic materials. Commonly used permanent magnetic materials include AlNiCo permanent magnetic alloys, ferrite permanent magnets, rare earth permanent magnets and various composite permanent magnetic materials. Permanent ferrite is one of the basic functional materials of permanent magnet DC motors. It can meet the use requirements of motors in various environments. It has high sensitivity and stability and can be widely used in various types of high-power, high-speed, high-torque motors, such as high-end automotive motors (ABS motors, starter motors, etc.), motorcycle starter motors, household appliances, and electric tool motors.

[0003] Permanent ferrite can be divided into strontium ferrite and barium ferrite according to chemical composition, and can be divided into sintered permanent ferrite and bonded permanent ferrite according to manufacturing process. Sintered permanent ferrite is made by molding permanent ferrite powder in a magnetic field and then sintering it at high temperature. Sintered permanent ferrite can be divided into dry molding and wet molding according to different molding methods. During wet molding, ferrite powder is surrounded by a dispersion medium (water or alcohol). Due to the presence of the dispersion medium, the powder is easy to rotate in the magnetic field, and can obtain a good orientation degree, and the product performance is high. However, since the dispersion medium needs to be discharged during the molding process, the molding efficiency is low. Dry molding is to mix ferrite powder and binder evenly, and then mold them directly in a magnetic field. The molding efficiency is high, the molding device is simple, and it is particularly suitable for the production of some products with complex shapes and small sizes. However, since there is no dispersion medium between the powder particles, the friction between the particles increases, which is not conducive to the rotation of the powder in the magnetic field, resulting in a relatively poor orientation degree, and it is difficult to obtain high remanence, resulting in lower product performance than wet pressing. In addition, the surface of the dry-formed blank is smooth and flat, and no trimming is required, which greatly reduces the amount of grinding and processing, making it more advantageous than the wet pressing method.

[0004] With the increasing development of electronic information technology, various electronic devices have higher and higher requirements for the magnetic functional components that match them, which is specifically manifested in increasingly complex shapes, gradually reduced volumes, and increasingly higher processing precision. Generally speaking, to improve the magnetic properties of dry-pressed products, we can start from two aspects: one is to start with raw materials and use pre-burned materials with higher performance; the other is to start with powder making and molding processes, by improving the dispersibility of dry-pressed powders, reducing the adhesion between particles, and selecting suitable binders to improve the fluidity of powders, thereby improving the orientation of magnetic powders during magnetic field molding.

[0005] Chinese patents CN112679215A, CN112521171B and CN111354526B respectively studied the use of activated carbon binder, polyvinyl alcohol aqueous solution and plant glue to replace conventional camphor as magnetic powder binder, which not only improved the orientation of magnetic powder in magnetic field forming, but also improved the mass production conditions and avoided the impact of camphor volatile odor on workers' health. Chinese patent CN112908676A uses high-speed dispersing equipment to fully break up and disperse magnetic powder, thereby improving the dispersion characteristics of magnetic powder, thereby obtaining a higher orientation degree in magnetic field forming and improving the magnetic properties of the material.

[0006] However, the use of organic matter as a binder in the above-mentioned prior art brings a series of disadvantages and risks to the preparation of magnets, mainly including: (1) the addition of organic binders makes it difficult for the magnets to be completely decomposed during the sintering process, and the residues will cause dark cracks in the magnets, affecting the strength of the magnets; (2) the gradual decomposition and volatilization of organic matter during the sintering process of the magnets leaves a small number of holes in the magnets, thereby causing the density of the magnets to decrease and reducing the material performance; (3) some organic binders decompose and volatilize to emit harmful gases, posing environmental risks, etc. Therefore, how to eliminate the disadvantages and risks existing in the above-mentioned prior art during the preparation process is crucial to the development of magnetic materials. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing an anisotropic permanent ferrite magnet and a permanent ferrite, which does not require the addition of an organic binder. By adding an appropriate amount of solid lubricant to pre-magnetized magnetic powder and controlling the water content of the magnetic powder, a high-performance dry-pressed anisotropic sintered magnet can be obtained.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing an anisotropic permanent ferrite magnet, the preparation method comprising:

[0010] (I) pre-magnetizing the magnetic powder raw material to obtain pre-magnetized magnetic powder;

[0011] (II) adding a lubricant to the pre-magnetized magnetic powder for primary mixing, and then adding a dispersion medium for secondary mixing to obtain heterogeneous magnetic powder;

[0012] (III) dry pressing the heterogeneous magnetic powder in a magnetic field to form a heterogeneous magnetic blank, and then heat treating it to obtain a permanent ferrite.

[0013] The present invention performs pre-magnetization treatment on magnetic powder raw materials so that the magnetic powder maintains a sufficient degree of orientation during dry pressing magnetic field forming, thereby obtaining better magnetic properties; at the same time, by adding solid lubricants, the fluidity of the magnetic powder is improved, thereby ensuring the uniformity of magnetic powder filling during dry pressing forming, and facilitating the free rotation of the magnetic powder, thereby improving the forming orientation degree, without adding organic binders, so that the magnet is completely decomposed during the heat treatment process, and the problem of holes in the magnet causing density reduction can be avoided.

[0014] Furthermore, the preparation method provided by the present invention can prepare high-performance dry-pressed anisotropic magnets by optimizing the pre-magnetization process, reasonably adding lubricants, and further adding water as a binder. It is particularly suitable for preparing two-pole, four-pole, six-pole, eight-pole and full-radial dry-pressed anisotropic magnetic rings.

[0015] As a preferred technical solution of the present invention, the general formula of the magnetic powder raw material is: A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or a combination consisting of Sr and Ba; 0.15≤x≤0.35; 0.25≤y≤0.45; 0.10≤z≤0.35; 0.6≤z / y≤0.9; 5.2≤n≤5.8.

[0016] As a preferred technical solution of the present invention, in step (I), the pre-magnetization treatment comprises:

[0017] The magnetic powder raw material is mixed with the additive and wet ball milled to obtain magnetic powder slurry, and the magnetic powder slurry is wet pre-magnetized to obtain a pre-magnetized blank, and then the pre-magnetized blank is dried and crushed to obtain the pre-magnetized magnetic powder.

[0018] Preferably, the method further comprises: performing a screening process after completing the crushing.

[0019] Preferably, the primary screening process uses a 20-50 mesh sieve, and the mesh size of the sieve can be, for example, 20 mesh, 25 mesh, 28 mesh, 30 mesh, 35 mesh, 38 mesh, 40 mesh, 45 mesh, 48 mesh or 50 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] As a preferred technical solution of the present invention, the additive includes any one of SiO2, CaCO3, ZnO or SrCO3 or a combination of at least two of them, wherein typical but non-limiting combinations are: a combination of SiO2 and CaCO3, a combination of SiO2, CaCO3 and SrCO3, a combination of SiO2, ZnO and SrCO3, a combination of SiO2, CaCO3, ZnO and SrCO3, and the like.

[0021] Preferably, the average particle size of the additive is ≤5 μm.

[0022] Preferably, the total mass of the magnetic powder raw material and the additive is recorded as 100%, the mass fraction of SiO2 is 0.2-1.0%; the mass fraction of CaCO3 is 0.4-2.0%; the mass fraction of ZnO is 0-0.6%; and the mass fraction of SrCO3 is 0.1-1.0%.

[0023] The mass fraction of SiO2 may be, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] The mass fraction of CaCO3 can be, for example, 0.4%, 0.5%, 0.6%, 0.8%, 0.9%, 1.0%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] The mass fraction of ZnO can be, for example, 0%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, or 0.6%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0026] The mass fraction of SrCO3 can be, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] It should be noted that the mass fraction of ZnO may be, for example, 0%, which means that the additive does not contain ZnO, that is, the additive is a combination of SiO2, CaCO3 and SrCO3.

[0028] Preferably, the additive is a combination of SiO2, CaCO3, ZnO and SrCO3.

[0029] As a preferred technical solution of the present invention, the average particle size of the ferrite particles in the magnetic powder slurry is 0.8-1.0 μm, for example, it can be 0.8 μm, 0.82 μm, 0.85 μm, 0.88 μm, 0.9 μm, 0.93 μm, 0.95 μm, 0.98 μm or 1.0 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the magnetic field strength of the wet pre-magnetization molding is ≥6000Oe, and more preferably ≥8000Oe.

[0031] It should be noted that the present invention controls the magnetic field intensity of wet pre-magnetization molding to improve the orientation degree during pre-magnetization molding, ensure that sufficient orientation degree is maintained in subsequent dry pressing magnetic field molding, and thus obtain better magnetic properties.

[0032] Preferably, the moisture content of the pre-magnetized magnetic powder is ≤0.5wt%.

[0033] Preferably, the drying temperature is 90-110°C, for example, it can be 90°C, 93°C, 95°C, 98°C, 100°C, 102°C, 105°C, 108°C or 110°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] As a preferred technical solution of the present invention, in step (II), the lubricant includes an organic lubricant and / or an inorganic lubricant.

[0035] Preferably, the organic lubricant comprises stearate and / or paraffin powder.

[0036] Preferably, the stearate comprises any one of zinc stearate, calcium stearate or magnesium stearate, or a combination of at least two thereof, wherein typical but non-limiting combinations are: a combination of zinc stearate and calcium stearate, a combination of calcium stearate or magnesium stearate, a combination of zinc stearate and magnesium stearate, a combination of zinc stearate, calcium stearate and magnesium stearate, and the like.

[0037] Preferably, the inorganic lubricant comprises talc and / or calcium carbonate.

[0038] Preferably, the lubricant includes an organic lubricant and an inorganic lubricant.

[0039] Preferably, the total mass of the pre-magnetized magnetic powder and the lubricant is recorded as 100%, the mass fraction of the organic lubricant is 0.3-0.8%, and the mass fraction of the inorganic lubricant is 0.2-0.8%.

[0040] The mass fraction of the organic lubricant may be, for example, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or 0.8%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0041] It should be noted that the organic lubricant in the present invention is gradually decomposed and oxidized during the heating stage of the heat treatment and is completely eliminated, which easily leaves a small amount of pores in the magnet. When the total amount of organic lubricant added is too high, more pores are left after decomposition, affecting the product density and even causing the magnet to crack.

[0042] The mass fraction of the inorganic lubricant is 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or 0.8%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] The lubricant added in the present invention can improve the fluidity of the magnetic powder, thereby ensuring the uniformity of the magnetic powder filling during dry pressing magnetic field forming. At the same time, the improvement of the fluidity of the magnetic powder is also conducive to the free rotation of the magnetic powder during the forming process, thereby improving the forming orientation. In the dry pressing magnetic field forming process of the present invention, as the pressure and temperature increase, the organic lubricant can locally produce liquid, increase the fluidity of the magnetic powder, and at the same time produce viscosity after the forming is completed, playing the role of a binder; the inorganic lubricant not only plays the role of lubrication to isolate the magnetic powder during forming, but also can be decomposed in the subsequent heat treatment process to obtain active alumina, calcium oxide, etc. as a grain boundary flux of ferrite grains, thereby improving the comprehensive magnetic properties of ferrite.

[0044] As a preferred technical solution of the present invention, in step (II), the dispersion medium includes water.

[0045] Preferably, the dispersion medium is added to the pre-magnetized magnetic powder by spraying.

[0046] Preferably, the method further comprises: after completing the secondary mixing, performing a secondary screening process to obtain the heterogeneous magnetic powder.

[0047] Preferably, the secondary screening process uses a 20-50 mesh sieve, and the mesh size of the sieve can be, for example, 20 mesh, 25 mesh, 28 mesh, 30 mesh, 35 mesh, 38 mesh, 40 mesh, 45 mesh, 48 mesh or 50 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the moisture content of the anisotropic magnetic powder is 3-5wt%, for example, it can be 3wt%, 3.2wt%, 3.5wt%, 3.6wt%, 3.8wt%, 4wt%, 4.3wt%, 4.5wt%, 4.6wt%, 4.8wt%, 4.9wt% or 5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, and it is further preferably 3.5-4.8wt%.

[0049] It should be noted that the present invention controls the moisture content of the heterogeneous magnetic powder. When the moisture content is too low, the strength of the formed magnet deteriorates and it is easy to crack after heat treatment. When the moisture content is too high, the fluidity of the magnetic powder during the dry pressing magnetic field forming process deteriorates, affecting the orientation of the magnetic powder during forming, resulting in relatively low magnetic properties after heat treatment.

[0050] The invention adds water to the pre-magnetized magnetic powder to improve the cohesiveness of the magnetic powder, ensures that the formed magnet has a certain strength, and evenly distributes the water in the magnetic powder through stirring and mixing, and granulates the magnetic powder to improve the fluidity of the magnetic powder.

[0051] As a preferred technical solution of the present invention, in step (II), the rotation speeds of the primary mixing and the secondary mixing are independently ≥100 r / min.

[0052] Preferably, the time for the primary mixing and the secondary mixing is independently 20 to 50 min, for example, 20 min, 23 min, 25 min, 30 min, 35 min, 40 min, 45 min, 48 min or 50 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] The primary mixing of the present invention is carried out by stirring with a high-speed mixer to ensure that the lubricant in the magnetic powder is evenly dispersed. The secondary mixing can be carried out by stirring with a stirrer first, and further by mixing with a high-speed mixer to ensure that the water content is as uniform as possible.

[0054] The lubricant added in the present invention, especially the organic lubricant, needs to be dispersed evenly. If there are too many residues that are not evenly dispersed in the molded magnetic powder, relatively large holes will be left in the magnet after heat treatment, affecting the product density and even causing the magnet to crack. At the same time, the fluidity of the magnetic powder is reduced, resulting in uneven local density of the molded blank, cracking after heat treatment, and reducing the strength of the magnet.

[0055] As a preferred technical solution of the present invention, in step (III), the magnetic field strength of the dry pressing magnetic field forming is 6000-10000Oe, for example, it can be 6000Oe, 6500Oe, 6800Oe, 7000Oe, 7500Oe, 7800Oe, 8000Oe, 8500Oe, 8800Oe, 9000Oe, 9500Oe, 9800Oe or 10000Oe, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In the dry-pressed magnetic field forming of the present invention, a special mold is designed according to different product requirements, including but not limited to the preparation of two-pole, four-pole, six-level, eight-level or full radial magnetic rings and other special specifications of products, and the magnetic properties must be taken into account according to the actual needs of the magnet to avoid cracking during the subsequent heat treatment process. When the magnetic field strength of the dry-pressed magnetic field forming is lower than 6000Oe, the magnetic powder is difficult to orient during the forming process, resulting in relatively low magnetic properties of the product; when the magnetic field strength of the dry-pressed magnetic field forming is higher than 10000Oe, the forming process will generate greater stress in the blank, which will cause the magnet to crack during the subsequent heat treatment process.

[0057] The present invention adopts a track electric kiln, a natural gas kiln or a box-type resistance furnace to sinter the formed blank.

[0058] Preferably, the heat treatment comprises: sequentially performing a heating treatment, a low-temperature heat preservation treatment and a high-temperature sintering on the heterogeneous magnet blank.

[0059] Preferably, the heating rate of the heating treatment is ≤5°C / min.

[0060] Preferably, the temperature of the low-temperature insulation treatment is 280-350°C, for example, it can be 280°C, 285°C, 290°C, 295°C, 300°C, 310°C, 315°C, 320°C, 330°C, 340°C or 350°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] Preferably, the low-temperature insulation treatment time is 1 to 3 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc. Other values ​​not listed in this numerical range are also applicable.

[0062] Preferably, the high temperature sintering temperature is 1200-1280°C, for example, it can be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C or 1280°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] Preferably, the high temperature sintering time is 1 to 5 hours, for example, it can be 1h, 1.2h, 1.5h, 1.6h, 1.8h, 2h, 2.5h, 2.8h, 3h, 3.5h, 3.8h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] After the heat preservation stage of high-temperature sintering is finished, the invention cools naturally to room temperature along with the furnace, and then grinds the upper and lower surfaces of the sintered magnet to obtain dry-pressed heterogeneous sintered permanent ferrite.

[0065] In the sintering process of the present invention, the added organic lubricant and water gradually volatilize and decompose. If the heating speed is too fast, the water and organic lubricant volatilize and decompose too fast, which easily leaves holes in the magnet and accumulates stress, thereby causing the magnet to heat up and crack. The present invention is heat-insulated for a period of time under low temperature conditions of 280 to 350° C., which is conducive to the decomposition and volatilization of the organic lubricant and avoids the magnet from heating up and cracking.

[0066] In a second aspect, the present invention provides a permanent ferrite, which is prepared by the method for preparing the anisotropic permanent ferrite magnet described in the first aspect.

[0067] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] (1) The present invention provides a method for preparing an anisotropic permanent ferrite magnet and a permanent ferrite, which improves the magnetic properties of the dry-pressed anisotropic magnet by optimizing the pre-magnetization process and reasonably adding a lubricant;

[0070] (2) Due to the uniform distribution of the added lubricant and moisture, there are fewer dark cracks inside the magnet, and the use of a reasonable heat treatment process reduces stress damage and the risk of magnet cracking, which is significantly better than similar dry-pressed anisotropic magnets prepared by traditional processes;

[0071] (3) The present invention does not need to add toxic organic substances with special odors such as camphor as binders, is green and environmentally friendly, and can achieve mass production. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0073] In a specific embodiment, the present invention provides a method for preparing an anisotropic permanent ferrite magnet, the preparation method comprising:

[0074] (1) mixing a magnetic powder raw material and an additive and performing wet ball milling to obtain a magnetic powder slurry, wherein the average particle size of the ferrite particles in the magnetic powder slurry is 0.8 to 1.0 μm, and performing wet pre-magnetization molding on the magnetic powder slurry under the condition of a magnetic field strength of ≥6000 Oe to obtain a pre-magnetized blank, then drying the pre-magnetized blank at a temperature of 90 to 110° C., crushing it with a crusher, and then sieving it once with a 20 to 50 mesh screen to obtain a pre-magnetized magnetic powder with a moisture content of ≤0.5wt%;

[0075] The general formula of the magnetic powder raw material used is: A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or a combination of Sr and Ba; 0.15≤x≤0.35; 0.25≤y≤0.45; 0.10≤z≤0.35; 0.6≤z / y≤0.9; 5.2≤n≤5.8, and the additive includes any one of SiO2, CaCO3, ZnO or SrCO3 or a combination of at least two thereof;

[0076] (2) adding an organic lubricant and / or an inorganic lubricant to the pre-magnetized magnetic powder, and mixing the pre-magnetized magnetic powder for 20 to 50 minutes at a rotation speed of ≥100 r / min to make the powder uniformly dispersed;

[0077] (3) then adding water for secondary mixing to make the water evenly distributed, and then using a 20-50 mesh screen to perform secondary sieving to obtain anisotropic magnetic powder, and controlling its water content to be 3-5wt%;

[0078] (4) filling the mold with heterogeneous magnetic powder and applying a magnetic field of 6000 to 10000 Oe to perform dry pressing magnetic field molding so that all the magnetic powders are arranged along the easy magnetization direction and the molding pressure is 7 to 9 MPa to obtain a heterogeneous magnet blank;

[0079] (5) The anisotropic magnet blank is subjected to a heating treatment at a heating rate of ≤5°C / min, and is subjected to a low-temperature insulation treatment at 280-350°C for 1-3 hours, followed by a high-temperature sintering treatment at a sintering temperature of 1200-1280°C and insulation treatment for 1-5 hours. After the high-temperature sintering is completed, the blank is naturally cooled to room temperature in the furnace to obtain a permanent magnet ferrite.

[0080] Example 1

[0081] This embodiment provides a method for preparing an anisotropic permanent ferrite magnet, which specifically includes the following steps:

[0082] (1) mixing a magnetic powder raw material and an additive and performing wet ball milling to obtain a magnetic powder slurry, wherein the average particle size of the ferrite particles in the magnetic powder slurry is 0.85 μm, and performing wet pre-magnetization molding on the magnetic powder slurry under a magnetic field strength of 8000 Oe to obtain a pre-magnetized blank, then drying the pre-magnetized blank at 100° C., crushing it with a crusher, and then sieving it once with a 50-mesh sieve to obtain a pre-magnetized magnetic powder with a moisture content of 0.38 wt %;

[0083] Among them, the main phase of the magnetic powder raw material is Sr 0.25 Ca 0.3 La 0.45 Fe 11.1 Co 0.32 O 19 The permanent magnet ferrite powder, the additive is a combination of SiO2, CaCO3, ZnO and SrCO3, the total mass of the magnetic powder raw material and the additive is recorded as 100%, the mass fraction of SiO2 is 0.5%; the mass fraction of CaCO3 is 1.5%; the mass fraction of ZnO is 0.2%; the mass fraction of SrCO3 is 0.2%;

[0084] (2) Adding lubricants as shown in Table 1 to the pre-magnetized magnetic powder, and mixing them once at 300 r / min for 20 min using a high-speed mixer;

[0085] (3) Then, a proper amount of water was added by spraying, and the mixture was continuously stirred in a mixer. A high-speed mixer was further used for secondary mixing at 300 r / min for 30 min to make the water evenly distributed. A 30-mesh sieve was used for secondary sieving to obtain heterogeneous magnetic powder. The water content of the powder was tested. The results are shown in Table 1.

[0086] (4) On a 45T test molding press, the anisotropic magnetic powder is filled into the mold, and a magnetic field of 8000Oe is applied to perform dry pressing magnetic field molding so that all the magnetic powders are arranged along the easy magnetization direction. The molding pressure is 8MPa to obtain anisotropic magnet blanks;

[0087] (5) The anisotropic magnet blank is subjected to a heating treatment at a heating rate of 5°C / min, and is subjected to a low-temperature insulation treatment at 300°C for 3 hours, followed by a high-temperature sintering treatment at a sintering temperature of 1250°C and insulation treatment for 2 hours. After the high-temperature sintering is completed, the blank is naturally cooled to room temperature in the furnace to obtain a permanent magnet ferrite.

[0088] Example 2

[0089] This embodiment provides a method for preparing an anisotropic permanent ferrite magnet, which specifically includes the following steps:

[0090] (1) mixing a magnetic powder raw material and an additive and performing wet ball milling to obtain a magnetic powder slurry, wherein the average particle size of the ferrite particles in the magnetic powder slurry is 0.8 μm, and performing wet pre-magnetization molding on the magnetic powder slurry under a magnetic field strength of 6000 Oe to obtain a pre-magnetized blank, then drying the pre-magnetized blank at 95° C., crushing it with a crusher, and then sieving it once with a 40-mesh screen to obtain a pre-magnetized magnetic powder with a moisture content of 0.4 wt%;

[0091] Among them, the main phase of the magnetic powder raw material is Sr 0.15 Ca 0.45 La 0.4 Fe 11.0 Co 0.28 O 19 The permanent magnet ferrite powder, the additive is a combination of SiO2, CaCO3, ZnO and SrCO3, the total mass of the magnetic powder raw material and the additive is recorded as 100%, the mass fraction of SiO2 is 0.2%; the mass fraction of CaCO3 is 2%; the mass fraction of ZnO is 0.6%; the mass fraction of SrCO3 is 0.6%;

[0092] (2) Adding lubricants as shown in Table 1 to the pre-magnetized magnetic powder, and mixing them once at 200 r / min for 30 min using a high-speed mixer;

[0093] (3) Then, a proper amount of water was added by spraying, and the mixture was stirred continuously in a mixer. A secondary mixing was performed for 50 min at 250 r / min in a high-speed mixer to make the water evenly distributed. The mixture was then sieved for a second time using a 30-mesh sieve to obtain anisotropic magnetic powder. The water content of the powder was tested. The results are shown in Table 1.

[0094] (4) On a 45T test molding press, anisotropic magnetic powder is filled into a mold, and a magnetic field of 6500Oe is applied to perform dry pressing magnetic field molding so that all the magnetic powders are arranged along the easy magnetization direction. The molding pressure is 7MPa to obtain anisotropic magnet blanks;

[0095] (5) The anisotropic magnet blank is subjected to a heating treatment at a heating rate of 4°C / min, and is subjected to a low-temperature insulation treatment at 350°C for 1 hour, followed by a high-temperature sintering treatment at a sintering temperature of 1200°C and insulation treatment for 3 hours. After the high-temperature sintering is completed, the blank is naturally cooled to room temperature in the furnace to obtain a permanent magnet ferrite.

[0096] Example 3

[0097] This embodiment provides a method for preparing an anisotropic permanent ferrite magnet, which specifically includes the following steps:

[0098] (1) mixing a magnetic powder raw material and an additive and performing wet ball milling to obtain a magnetic powder slurry, wherein the average particle size of the ferrite particles in the magnetic powder slurry is 1 μm, and wet pre-magnetizing the magnetic powder slurry under a magnetic field strength of 9000 Oe to obtain a pre-magnetized blank, then drying the pre-magnetized blank at 110° C., crushing it with a crusher, and then sieving it once with a 20-mesh screen to obtain a pre-magnetized magnetic powder with a moisture content of 0.45 wt %;

[0099] Among them, the main phase of the magnetic powder raw material is Sr 0.32 Ca 0.25 La 0.33 Fe 11.3 Co 0.25 O 19 The permanent magnet ferrite powder, the additive is a combination of SiO2, CaCO3, ZnO and SrCO3, the total mass of the magnetic powder raw material and the additive is recorded as 100%, the mass fraction of SiO2 is 0.2%; the mass fraction of CaCO3 is 2%; the mass fraction of ZnO is 0.5%; the mass fraction of SrCO3 is 1%;

[0100] (2) Adding lubricants as shown in Table 1 to the pre-magnetized magnetic powder, and mixing them once at 200 r / min for 50 min using a high-speed mixer;

[0101] (3) Then, a proper amount of water was added by spraying, and the mixture was stirred continuously in a mixer. A high-speed mixer was further used for secondary mixing at 200 r / min for 50 min to make the water evenly distributed. A 40-mesh sieve was used for secondary sieving to obtain heterogeneous magnetic powder. The water content of the powder was tested. The results are shown in Table 1.

[0102] (4) On a 45T test molding press, fill the mold with heterogeneous magnetic powder and apply a magnetic field of 10000Oe to perform dry pressing magnetic field molding so that all the magnetic powders are arranged along the easy magnetization direction. The molding pressure is 9MPa to obtain a heterogeneous magnet blank;

[0103] (5) The anisotropic magnet blank is subjected to a heating treatment at a heating rate of 3°C / min, and is subjected to a low-temperature insulation treatment at 280°C for 2 hours, followed by a high-temperature sintering treatment at a sintering temperature of 1280°C and insulation treatment for 1 hour. After the high-temperature sintering is completed, the blank is naturally cooled to room temperature in the furnace to obtain a permanent magnet ferrite.

[0104] Example 4

[0105] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0106] Example 5

[0107] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0108] Example 6

[0109] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the components and contents of the additives in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0110] Example 7

[0111] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0112] Example 8

[0113] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0114] Example 9

[0115] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0116] Example 10

[0117] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that the composition and content of the lubricant in step (2) are different, as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0118] Embodiment 11

[0119] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that no organic lubricant is added to the lubricant in step (2), as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0120] Example 12

[0121] This embodiment provides a method for preparing anisotropic permanent ferrite magnets, which differs from Embodiment 1 in that no inorganic lubricant is added to the lubricant in step (2), as shown in Table 1, and the remaining process parameters and operating conditions are the same as those in Embodiment 1.

[0122] Example 13

[0123] This embodiment provides a method for preparing a permanent ferrite magnet, which differs from Embodiment 1 in that: in step (3), after adding a proper amount of water, the moisture content of the heterogeneous magnetic powder is detected to be 0.55wt%, and the other process parameters and operating conditions are the same as those in Embodiment 1.

[0124] Embodiment 14

[0125] This embodiment provides a method for preparing a permanent ferrite magnet, which differs from Embodiment 1 in that: in step (3), after adding a proper amount of water, the moisture content of the heterogeneous magnetic powder is detected to be 0.23wt%, and the other process parameters and operating conditions are the same as those in Embodiment 1.

[0126] The present invention grinds the upper and lower surfaces of the permanent ferrites obtained in Examples 1 to 14, and measures the residual magnetic induction intensity Br, surface magnetism, coercive force Hcj, magnetic strength and yield rate at room temperature (20°C). The results are shown in Table 2.

[0127] Table 1

[0128]

[0129] Table 2

[0130]

[0131] It can be seen from the contents of Table 1 and Table 2 that when at least one organic lubricant and one inorganic lubricant are added in Examples 1 to 10, and the respective addition amounts are controlled at 0.5 to 0.8 wt% and 0.3 to 0.8 wt% respectively, and the moisture content is controlled at 3 to 5 wt%, the prepared dry-pressed anisotropic magnets obtain better magnetic properties, and at the same time, the magnet strength and yield rate are relatively ideal.

[0132] By comparing Example 1, Example 11 and Example 12, it is not difficult to see that when only one lubricant (only organic lubricant or inorganic lubricant) is added during the preparation process, the magnetic properties of the permanent ferrite magnet obtained are significantly reduced, and the magnet strength cannot meet the requirements, and cracking is prone to occur, resulting in a reduction in the yield.

[0133] It can be seen from Table 2 that compared with Example 1, since the moisture content is not controlled in Example 13 and Example 14, the moisture content of the magnetic powder exceeds the range of 3-5wt%, resulting in an overall decrease in the magnetic properties of the permanent ferrite magnets and failing to meet the requirements.

[0134] Compared with the traditional preparation method that uses polyethylene, camphor, etc. as magnetic powder binders, which easily cause dark cracks in the magnet and lead to a decrease in the yield, the magnetic powder raw materials in the present invention are completely decomposed during the heat treatment process to avoid dark cracks in the magnet, effectively improve the yield, and do not need to use organic binders to prevent the decomposition of harmful gases that threaten the environment and the safety of operators.

[0135] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing anisotropic permanent ferrite magnets, characterized in that: The preparation method comprises: (I) pre-magnetizing the magnetic powder raw material to obtain pre-magnetized magnetic powder; (II) adding a lubricant to the pre-magnetized magnetic powder for primary mixing, and then adding a dispersion medium for secondary mixing to obtain heterogeneous magnetic powder; (III) dry pressing the heterogeneous magnetic powder in a magnetic field to form a heterogeneous magnetic blank, and then heat treating it to obtain a permanent ferrite.

2. The preparation method according to claim 1, characterized in that: The general formula of the magnetic powder raw material is: 1-x- y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or a combination consisting of Sr and Ba; 0.15≤x≤0.35; 0.25≤y≤0.45; 0.10≤z≤0.35; 0.6≤z / y≤0.9; 5.2≤n≤5.

8.

3. The preparation method according to claim 1 or 2, characterized in that: In step (I), the pre-magnetization treatment comprises: The magnetic powder raw material is mixed with the additive and wet ball milled to obtain magnetic powder slurry, and the magnetic powder slurry is wet pre-magnetized to obtain a pre-magnetized blank, and then the pre-magnetized blank is dried and crushed to obtain the pre-magnetized magnetic powder; Preferably, the method further comprises: after the crushing is completed, performing a screening process; Preferably, the primary screening process uses a 20-50 mesh sieve.

4. The preparation method according to claim 2 or 3, characterized in that: The additive includes any one of SiO2, CaCO3, ZnO or SrCO3 or a combination of at least two; Preferably, the average particle size of the additive is ≤5 μm; Preferably, the total mass of the magnetic powder raw material and the additive is recorded as 100%, the mass fraction of SiO2 is 0.2-1.0%; the mass fraction of CaCO3 is 0.4-2.0%; the mass fraction of ZnO is 0-0.6%; and the mass fraction of SrCO3 is 0.1-1.0%.

5. The preparation method according to claim 3 or 4, characterized in that: The average particle size of the ferrite particles in the magnetic powder slurry is 0.8 to 1.0 μm; Preferably, the magnetic field strength of the wet pre-magnetization molding is ≥6000Oe, and more preferably ≥8000Oe; Preferably, the moisture content of the pre-magnetized magnetic powder is ≤0.5wt%; Preferably, the drying temperature is 90-110°C.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (II), the lubricant includes an organic lubricant and / or an inorganic lubricant; Preferably, the organic lubricant comprises stearate and / or paraffin powder; Preferably, the stearate comprises any one of zinc stearate, calcium stearate or magnesium stearate, or a combination of at least two thereof; Preferably, the inorganic lubricant comprises talc and / or calcium carbonate; Preferably, the lubricant includes an organic lubricant and an inorganic lubricant; Preferably, the total mass of the pre-magnetized magnetic powder and the lubricant is recorded as 100%, the mass fraction of the organic lubricant is 0.3-0.8%, and the mass fraction of the inorganic lubricant is 0.2-0.8%.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (II), the dispersion medium comprises water; Preferably, the dispersion medium is added to the pre-magnetized magnetic powder by spraying; Preferably, the method further comprises: after the secondary mixing is completed, performing a secondary screening process to obtain the heterogeneous magnetic powder; Preferably, the secondary screening process uses a 20-50 mesh screen; Preferably, the water content of the heterogeneous magnetic powder is 3-5wt%.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (II), the rotation speeds of the primary mixing and the secondary mixing are independently ≥100 r / min; Preferably, the time for the primary mixing and the secondary mixing is independently 20 to 50 minutes.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (III), the magnetic field strength of the dry pressing magnetic field forming is 6000 to 10000 Oe; Preferably, the pressure of the dry pressing magnetic field molding is 7-9 MPa; Preferably, the heat treatment comprises: sequentially performing a heating treatment, a low-temperature heat preservation treatment and a high-temperature sintering on the heterogeneous magnet blank; Preferably, the heating rate of the heating treatment is ≤5°C / min; Preferably, the temperature of the low temperature insulation treatment is 280-350°C; Preferably, the low temperature insulation treatment time is 1 to 3 hours; Preferably, the high temperature sintering temperature is 1200-1280°C; Preferably, the high temperature sintering time is 1 to 5 hours.

10. A permanent magnetic ferrite, characterized in that: The permanent ferrite is prepared by the method for preparing anisotropic permanent ferrite magnets according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for manufacturing dry-pressed anisotropic sintered ferrite

    CN111354526B

  • Anisotropic permanent magnet ferrite and its preparation method

    CN112521171B

  • Method for dry pressing molding of permanent magnetic ferrite

    CN112679215A

  • Permanent magnetic ferrite magnetic powder for dry pressing and preparation method thereof

    CN112908676A